Up‐regulation of ZFAS1 indicates dismal prognosis for cholangiocarcinoma and promotes proliferation and metastasis by modulating USF1 via miR‐296‐5p. Issue 12 (29th September 2019) - Li, Zhenglong; Jiang, Xingming; Huang, Lining; Li, Jinglin; Ji, Daolin; Xu, Yi; Leng, Kaiming; Cui, Yunfu
Abstract: LncRNAs has been demonstrated to modulate neoplastic development by modulating downstream miRNAs and functional genes. In this study, we aimed to detect the interaction among lncRNA ZFAS1 miR‐296‐5p and USF1. We explored the proliferation, migration and invasion of cholangiocarcinoma. The differentially expressed ZFAS1 was discovered in both tissues and cell lines by qRT‐PCR. The targeting relationship between miR‐296‐5p and ZFAS1 or USF1 was validated by dual‐luciferase assay. The impact of ZFAS1 on CCA cell proliferation was observed by CCK‐8 assay. The protein expression of USF1 was determined by Western blot. The effects of ZFAS1, miR‐296‐5p and USF1 on tumour growth were further confirmed using xenograft model. LncRNA ZFAS1 expression was relatively up‐regulated in tumour tissues and cells while miR‐296‐5p was significantly down‐regulated. Knockdown of ZFAS1 significantly suppressed tumour proliferation, migration, invasion and USF1 expression. Overexpressed miR‐296‐5p suppressed cell proliferation and metastasis. Knockdown of USF1 inhibited cell proliferation and metastasis and xenograft tumour growth. In conclusion, ZFAS1 might promote cholangiocarcinoma proliferation and metastasis by modulating USF1 via miR‐296‐5p.